Efektivitas Model Numbered Head Together (NHT) dengan Pendekatan Saintifik Terhadap Hasil Belajar Kimia Siswa - Zakiyah Ayu Noor Izzati; Farah Erika; Sri Lestari (Chemistry Education Practice, 2026)
The Numbered Head Together (NHT) learning model, with a scientific approach, emphasizes that student learning outcomes can increase student interest in learning. The purpose of this study was to determine the effectiveness of the NHT learning model, using a scientific approach, on student learning outcomes at SMA Negeri 8 Samarinda. This is a quantitative pre-experimental study using a one-group pretest-posttest design. The population of this study consisted of all students in class XI MIPA. Purposive sampling was used to obtain two research samples, namely XI 1 and XI 3, with a total of 69 students. Data were collected using test techniques, such as questions, and non-test techniques, such as observation sheets. The data analysis techniques used were the N-Gain test and the effect size test. The results showed that the average post-test score was 77.22, and student activity during the learning process was 84%, which falls in the very good category. The average N-Gain value was 0.74% in the high category, and the effect size value was 11.34 in the large category. It can be concluded that the Numbered Head Together (NHT) learning model, using a scientific approach, is effective in improving students' learning outcomes at SMA Negeri 8 Samarinda.